FLUCTUATING COMMODITY PRICES' EFFECT ON INDONESIAN COAL AND PALM OIL - Danny Jubel Abrian Sianturi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
This study examines the impact of fluctuating commodity prices on the stock volatility and financial performance of Indonesian coal and palm oil companies between 2011 and 2022. During the COVID-19 pandemic, commodity price fluctuations have significantly influenced these sectors. Using Vector Error Correction Model (VECM) and Dynamic Conditional Correlation Generalized Autoregressive Conditional Heteroskedasticity (DCC GARCH) approaches, as well as panel regression, this study analyzes price volatility and its effect on financial performance. The findings reveal distinct volatility patterns in the palm oil and coal industries, providing valuable insights for investors to understand the risks associated with price fluctuations and identify companies significantly affected by such volatility. This research contributes to understanding the relationship between fluctuations in commodity prices and stock prices of palm oil and coal companies, as well as their financial performance, in the context of the Indonesian economy, which relies heavily on these two commodities. By emphasizing the importance of understanding commodity price dynamics, this study provides valuable information for investor decision-making and risk management in the face of commodity price volatility.